(untitled) (Bangladesh Journal of Zoology, 2022)
Shrimp aquaculture plays the key role in Bangladesh seafood export industry. It includes the species of Tiger prawn Penaeus monodon, and Giant river prawn Macrobrachium rosenbergii, which have been widely farmed after 1980s. The industry is severely damaged due to diseases outbreaks in hatcheries, nurseries and grow-out ponds since 2000, thus this sector shows shrinkage from global export market. However, the last few decades an alternate aquaculture decapod species, Whiteleg shrimp Litopenaeus vannamei has been recognized as the most important in world-seafood export item. Bangladesh aquaculture has very recently been introduced with the Whiteleg shrimp L. vannamei for shrimp production boost up. This review focusses on the current state of arts for L. vannamei aquaculture techniques and their possible implication to farming in Bangladesh. Recently, several Whiteleg shrimp pilot scale farming were initiated which showed promising production ranged from 5.0 to 8.9 MT/ha. Private entrepreneurs now become interested and it is perceived that the Whiteleg shrimp could gear up shrimp production in near future in terms of better production performance, technology development and extension work besides other indigenous culture-shrimp species. By introducing this shrimp, we forecast that, depending upon the technology adoption in present culture areas, the export frozen seafood earnings from shrimp sector will increase up to 5 to 10 folds from the present. Thus, proper understanding and knowledge based innovative approach for its sustainable rapid extension and strategies is in need. This review suggests the regional reproducible pilot culture program for hatchery, nursery and grow-out under controlled environment ensuring better footprint and low residues impact to natural aquatic systems. Adaptive research should be initiated to develop intensive or super-intensive culture techniques besides the traditional practices in the selected confined areas. The pond culture, biofloc farming, aquamimicry farming and green water raceways could be excellent options for L. vannamei culture in Bangladesh. Bangladesh J. Zool. 50 (2): 143-184, 2022